ULTRASOUND-ASSISTED EXTRACTION OF OIL FROM KIWIFRUIT (Actinidia Deliciosa) SEEDS - COELHO, RENATA; KANDA, LUIS R. S.; HAMERSKI, FABIANE; ANDRADE, ERIEL F.; MASSON, MARIA LUCIA; CORAZZA, MARCOS L. (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
This study reports experimental kinetic data and modeling for the extraction of oil from kiwifruit seeds by ultrasound-assisted extraction (UAE) with ethanol. The fatty acid profile, tocopherol and total lipids content in the oil obtained were determined. The variables temperature and ultrasonic power were investigated based on the oil extraction yields using a central composite experimental design. The overall yields obtained were compared to conventional Soxhlet extraction with n-hexane and with ethanol. The extractions presented high extraction rates with overall yield ranged between 19 and 33%, and the extraction yields increased with the temperature. The fatty acid profile showed a high content of omega-3 fatty acids (63.20%) and the Vitamin E content was 14.97 ± 0.38 mg/100 g oil, with ɤ-tocopherol constituting 49% of the total tocopherol. A second-order kinetic model was applied to describe the ultrasound extraction process under different conditions. The numerical results were compared with the experimental extraction yields and presented a good correlation. The extraction technique investigated was found to be suitable for extraction of oil from kiwifruit seeds, in which the great potential of kiwifruit oil obtained from UAE was demonstrated